The perceivable changes to the audit profession in Vietnam in light of the 2025 IFRS adoption - Vũ, Phương Chi ([s.l.], 2020)
The adoption of International Financial Reporting Standards will bring about many significant changes to a developing economy such as Vietnam. One of those changes will be related to the labor force, such as regulators, practitioners, accountants, and auditors, among many others. It is expected that with different accounting standards, the job of accountants will change accordingly. But will it be the same for auditors? The common perception about the audit profession is that auditors evaluate evidence and documentation about clients’ business transactions and activities to ensure clients comply with relevant assertions (such as accuracy, completeness, existence, valuation, occurrence, classification, cut-off,…) in order to give an opinion about whether the financial statements are true and fair. Therefore, the accounting standards that the clients adopt should not affect the job of auditors because auditors only need to know if the company is doing what it says it is doing. The researchers decide to choose this topic we all wish to work in audit (in Vietnam or abroad) when we graduate; therefore, this topic is of utmost importance to us because it directly helps us understand our future jobs.